An Integrated View of Student Success at Small Colleges. Issue 184 (20th August 2020) - Palucki Blake, Laura; Wynn, T. Colleen
Abstract: Contemporary students have a varied set of needs—the "lifecycle" of a typical student may no longer be 4 years of continuous enrollment between the ages of 18 and 22, and many students bring rich and varied experiences with them to college. As institutions strive to allocate resources in ways that provide the most benefit to student achievement, creating a culture of evidence that not only deepens our understanding of students but also promotes institutional action has become more important than ever. This chapter articulates institutional research's collaborative role in integrating data and analytics in ways that support, engage, and enhance student experiences across the institution. Examples of how institutional research offices have collaborated with student affairs and information technology offices will be discussed. The chapter will conclude with a set of recommendations to assist institutional researchers in partnering across campus to share timely and relevant data to enhance student success.